Efektivitas Administrasi Dan Pengawasan Dalam Meningkatkan Kinerja Sekretariat Dprd Kabupaten Bintan - Nisa Aisyah; Dessy Natallia; Cahya Hari Sunarto; Adhe Fadli Farhan; Sumadio . (CV. ITTC INDONESIA, 2026)
This study is motivated by the problem of suboptimal administrative and supervisory support in strengthening the institutional performance of the Regional House of Representatives (DPRD), particularly at the regency level. This study aims to analyze the effectiveness of the administrative and supervisory functions in supporting the performance of the DPRD Secretariat of Bintan Regency, by examining the achievements, obstacles, and influencing factors of both functions. The research employs a qualitative method with a descriptive approach. Data were collected through semi-structured interviews, observation, and documentation involving seven purposively selected informants. The study was conducted at the DPRD Secretariat of Bintan Regency from February to April 2026. Data analysis used the interactive model of Miles and Huberman, with validity tested through source and method triangulation. The findings indicate that administrative functions have been implemented relatively well, although limitations in human resources and technology infrastructure remain. The supervisory function has been carried out but is not yet fully optimal due to its dependence on members’ meeting attendance. Improvements in human resource capacity, technology-based administrative systems, and inter-divisional coordination are necessary.